An innovative biomass-fueled gas turbine-ORC system equipped with electrochemically mediated amine regeneration (EMAR) for CO2 capture. (February 2023) - Hasanzadeh, Amirhossein; Mehrara, Mahsa; Irani, Milad; Chitsaz, Ata; Parham, Kiyan
Abstract: CO2 capture technologies can contribute to reducing pollutant emissions and achieving a ‎cleaner environment. ‎Despite the trend toward reducing fossil fuel use, many of the suggested alternatives emit substantial amounts of CO2, including biomass gasifiers. This study presents a novel hybrid power generation system consisting of a biomass gasifier, a gas turbine, an ORC cycle, an electrochemically mediated amine regeneration (EMAR) technology to capture CO2 emissions, and, for the final storage, a CO2 compressor. Clean production is the primary goal of this study, in which a large amount of energy is produced with a near zero CO2 emission, using EMAR CO2 capture technology. An energy-based model is presented and validated carefully. Two scenarios are proposed to assess the system feasibility encompassing parametric and optimization studies. During the parametric study, the influence of the three subsystems' (gas turbine, biomass gasifier, EMAR) parameters is investigated on three energy efficiencies, defined to evaluate the proposed system performance. Lastly, the hybrid system is optimized via Genetic algorithm considering each efficiency as the objective. Results illustrate that the maximum obtainable efficiency of the system without utilizing EMAR can reach up to 33.65%. Whereas utilizing EMAR and CO2 compressing lowers the efficiency by 6–8% (by point). Highlights: EMAR CO2 capture technology integration with a biomass-fueled GT-ORC was evaluated. Effect of EMAR, gasification, and gas turbine parameters were evaluated on the system. The system was optimized considering η 1, η 2, and η 3 as objectives. At η 3 -objective, the CCS lowered the system efficiency from 33.65% to 27.63%.